Preparation for Practice through Service User involvement in the Diagnostic Radiography curriculum at University Campus Suffolk - Strudwick, Ruth; Harvey-Lloyd, Jane (International Journal of Practice-based Learning in Health and Social Care, 2016)
The purpose of this small-scale study was to evaluate the student experience of service user involvement in the curriculum for the module entitled ‘The Service User’ as part of a BSc (Hons) Diagnostic Radiography degree programme. Following four teaching sessions, at which service users came to speak to the students about their experiences, a questionnaire was distributed to 43 second year diagnostic radiography students. Twenty-six responses were received (60%). The questionnaire was used to evaluate the usefulness of the sessions. A mixture of open and attitudinal questions using a seven point Likert scale was employed. The results were analysed and the feedback was generally positive in terms of the involvement of service users within the curriculum.